(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
Relying on universal democratic principles in society is the basis for raising it to the level of value. Here it is necessary to consider the connection and difference between the concepts of "principle" and "value". "Principle" is a set of viewpoints, behavior, political, economic, social, legal, spiritual and moral rules that determine the conditions and norms of development. And value means that it is recognized by society and becomes an important factor of development.